?? hoje o dia: o efeito da dupla modera????o da antecipa????o do arrependimento e da reat??ncia sobre o apelo ?? escassez. - Carvalho, Marcelo (2019)
The scarcity appeal is one of the most widely used ways to boost sales. The expectation of future scarcity of a given product generates a stimulus for the consumer. Scarcity-based messages, such as "last units" and "only today", reinforce this expectation of future scarcity. Consumers are also influenced by the possibility of regret in the future. Regret is brought about by comparing a result with the return that could be obtained by making a different choice. The anticipated regret is one of the decisive aspects of decision-making. Individuals can anticipate regrets as they evaluate the decision to make, wondering how they would feel after each option. However, consumers can also consider the persuasive effects of a promotion and understand that threatens their freedom of choice, creating ???psychological reactance???. Reactance is a state of motivation where cognitive and behavioral efforts are directed toward the restoration of threatened or eliminated freedom. The objective of this study was to observe the moderating effect of the anticipated regret on the relationship between the scarcity appeal and purchase intention, as well as the moderating effect of the reactance on the anticipated regret. For this, two experiments have been carried out, demonstrating that: a) the scarcity appeal increases the purchase intention; b) the anticipated regret moderates positively the relation between scarcity appeal and purchase intention; c) in a scarcity scenario, the interaction between reactance, anticipated regret and involvement leads to a greater purchase intention.